A função socioambiental, a teia de interesses e os deveres fundamentais ecológicos : em busca de novas leituras para a propriedade - Bortolini, Rafaela Emília (2014)
A contemporary analysis of property rights suggests a strengthening of ecological duties that belong to the holder of the right, especially in light of the constitutional command of the environmental function of property, which comprises a environmental content inside. Furthermore, the model of State Environmental Law, as embraced by the Brazilian Constitution of 1988, operates to require a shared responsibility between State and Society, for the purpose of ensuring protection of the environment to be effective and ensure their survival for future generations. Thus, we present the process of humanization and greening by which the institute is undergoing property, breaking with the classical liberal view according to which the property would be to institute a set of powers available to the holder. There is a recognition of the fundamental duties related to property rights, supported by the commandment of the environmental function, so as to give rise to the holder the right to adopt behaviors that take into account the multiple interests that permeate the property, as proposed by the metaphor of web of interest. Thus, it is concluded that there was no conflict between the environment and property, since it encompasses a environmental content in your body, and must recognize a new model of private ownership of property, qualified and reinterpreted by ecological duties.